Bahasa Inggris - Feni Abdullah; Yolan Dunggio; Mindy Eka Astuti (Journal of Health, Technology and Science (JHTS), 2022)
This research aims to identify the fungus that causes Tinea Ungium on the toenails of the Gorontalo City Environment Agency (DLH) workerThe method used in this study is a research approach qualitative descriptive observational. The type of data used is primary data in the form of research results and secondary data in the form of data from literature, books and documents as well as data from the Health Service and Environment Service of Gorontalo City. The sampling technique in this study used a purposive sampling technique, with a total of 10 samples.The results showed that the percentage of Tinea ungium infection on the toenails of DLH officers in Gorontalo City was 0% or no fungal species that caused Tinea ungium disease were found by producing varying colony colors oncolony culture methods, namely, brownish gray, white, brownish yellow, greenish yellow. Meanwhile, with the microscopic method, the results of the fungal species that cause Tinea unguium were obtained, including the following fungi: Rhizopus sp, Mucor sp, Aspergillus sp, and. With this research, it is hoped that waste officers can take early precautions against the fungus that causes tinea ungium.